Explosive force production during isometric squats correlates with athletic performance in rugby union players - Tillin, N. A.; Pain, M. T. G.; Folland, J. (Journal of Sports Sciences, 2013)
This study investigated the association between explosive force production during isometric squats and athletic performance (sprint time and countermovement jump height). Sprint time (5 and 20 m) and jump height were recorded in 18 male elite-standard varsity rugby union players. Participants also completed a series of maximal- and explosive-isometric squats to measure maximal force and explosive force at 50-ms intervals up to 250 ms from force onset. Sprint performance was related to early phase (=100 ms) explosive force normalised to maximal force (5 m, r = -0.63, P = 0.005; and 20 m, r = -0.54, P = 0.020), but jump height was related to later phase (>100 ms) absolute explosive force (0.51 < r < 0.61; 0.006 < P < 0.035). When participants were separated for 5-m sprint time (< or = 1s), the faster group had greater normalised explosive force in the first 150 ms of explosive-isometric squats (33-67%; 0.001 < P < 0.017). The results suggest that explosive force production during isometric squats was associated with athletic performance. Specifically, sprint performance was most strongly related to the proportion of maximal force achieved in the initial phase of explosive-isometric squats, whilst jump height was most strongly related to absolute force in the later phase of the explosive-isometric squats.